Optimization of Digital Marketing Strategy Through The Collaboration of Tokopedia and TikTok to Increase Brand Awareness and Sales of Bu Sarti’s Surabaya Specialty Shredded Beef - Ony Kurniawati; Richa Puspitasari; Mira Gayatri Kartika; Titok Waskito Adi; Davis Febrinanto Prakasa; Dedy Kunhadi (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This study aims to 1) Identify various internal factors that are the strengths and weaknesses faced by the Surabaya style Bu Sarti’s Shredded Beef MSME in an effort to increase brand awareness and product sales achievement; 2) Identify various external factors that have the potential to become opportunities or threats for the Surabaya style Bu Sarti’s Shredded Beef MSME in developing brand awareness and increasing sales volume amidst the dynamics of digital marketing; and Formulate an effective digital marketing strategy through collaboration between the Tokopedia and TikTok platforms, in order to encourage increased brand awareness and optimize sales of the Surabaya style Bu Sarti’s Shredded Beef MSME product. Design/methodology/approach: This research uses a qualitative approach, supported by quantitative data to support the analysis. Data collection was conducted through direct observation, structured interviews with relevant parties, questionnaire distribution, and document review related to the potential and challenges of implementing digital marketing through the collaboration between the Tokopedia and TikTok platforms. The informants involved in this research were: 1) TokoPedia sellers; 2) Creator or seller on TikTok; 3) Consumers (account owners on TikTok); and 4) Consumers (account holders at TokoPedia). The data obtained was then analyzed using the IFAS, EFAS, and SWOT matrices. The results of this analysis serve as the basis for formulating alternative digital marketing strategies appropriate to the business environment, which are expected to expand market reach, strengthen brand awareness, and drive sustainable product sales. Findings: The results of this study provide recommendations for developing marketing strategies, namely: 1) Improving the quality of digital promotional content; 2) Strengthening brand identity as a regional specialty; and 3) Utilizing collaboration with content creators or affiliates to expand promotional reach.